Significance of zinc-solubilizing plant growth-promoting rhizobacterial strains in nutrient acquisition, enhancement of growth, yield, and oil content of canola (Brassica napus L.) - Jalal-Ud-Din, Sabahet; Elahi, Nosheen Noor; Mubeen, Fathia (Frontiers in Microbiology, 2024)
Present research work was conducted with the aim to isolate, characterize and identify the promising zinc solubilizing rhizobacteria found naturally in the rhizosphere of canola (Brassica napus L.) plants. The study investigated the roles of these strains in nutrient acquisition and assimilation of extracellular molecules such as hormones and secondary metabolites. Ten isolated promising zinc solubilizing strains (CLS1, CLS2, CLS3, CLS6, CLS8, CLS9, CLS11, CLS12, CLS13 and CLS15) were selected and characterized biochemically. Almost all the tested strains were Gram positive, could fix nitrogen and positive for indole acetic acid, HCN, exopolysaccharides and siderophore production. These effective zinc solubilizing strains were identified through 16S rRNA gene sequencing. Based on amount of solubilized zinc and halo zone diameter, four potent strains (CLS1, CLS2, CLS3 and CLS9) were selected for pot and field evaluation. Among all the identified bacterial genera isolated from the rhizosphere of same host plant at different sampling sites, Priestia aryabhattai was found most abundant and found at all three sampling sites. The strains Priestia megaterium, Staphylococcus succinus and Bacillus cereus were found at two different sites. Bacillus subtilis was found at only one site. These strains have a number of plant growth stimulating characteristics as well as the ability to colonize plant roots successfully. The results indicated that inoculation of all these four zinc solubilizing tested strains enhanced the plant growth, oil contents and yield attributes of canola as compared to non-inoculated control with fertilizer levels. Staphylococcus succinus (CLS1) was first time reported as zinc solubilizer and associated with canola. Priestia aryabhattai (CLS2) and Priestia megaterium (CLS9) were found to be the best strains, with the most pronounced beneficial effect on canola growth and yield traits in both pot and field conditions. The site-specific dominance of these strains observed in this study may contribute towards decision making for development of specific inocula for canola. Therefore, identification of these strains could help in providing adequate amount of soluble zinc along with enhanced plants growth, yield and oil content of canola.